Prevalence of Earlobe Creases and Their Association With History of Cardiovascular Disease in Patients Undergoing Hemodialysis: A Cross‐Sectional Study. Issue 5 (7th September 2017) - Wakasugi, Minako; Kazama, Junichiro James; Kawamura, Kazuko; Yamamoto, Suguru; Nagai, Masaaki; Omori, Kentaro; Yokota, Saori; Fujikawa, Hirokazu; Aoike, Ikuo; Omori, Tsukasa; Narita, Ichiei
Abstract: Earlobe creases are surrogate markers for high risk of cardiovascular disease. There is no data concerning earlobe creases among hemodialysis patients, who have an increased risk of cardiovascular disease. A cross‐sectional study was conducted to determine the prevalence of earlobe creases and their association with prevalent cardiovascular disease among hemodialysis patients. Patients undergoing hemodialysis were recruited from five outpatient hemodialysis centers. Both earlobes were photographed during a dialysis session with the patient in a supine position and the photos evaluated independently by two experienced nephrologists blinded to the participants' clinical characteristics. Prevalent cardiovascular diseases were defined as a history of myocardial infarction, cerebrovascular accident, or peripheral vascular disease. Sensitivity, specificity, and positive and negative predictive values for detection of prevalent cardiovascular disease were calculated. Logistic analysis was used to examine the association between earlobe creases and prevalent cardiovascular disease. Earlobe creases were identified in 24.5% of 330 hemodialysis patients (200 men; mean age, 67.8 years). The prevalence of earlobe creases increased with age for men ( P for trend <0.0001), but not for women ( P for trend = 0.07). Sensitivity, specificity, and positive and negative predictive values were 30.9% (95% confidence interval, 21.9–41.6), 77.5% (71.9–82.3), 30.9% (21.9–41.6), and 77.5% (71.9–82.3), respectively. Multivariate logistic analyses indicated the prevalence of earlobe crease was not associated with prevalent cardiovascular diseases. The prevalence is similar to that previously reported for Japanese individuals not undergoing dialysis. No association between earlobe creases and prevalent cardiovascular diseases was identified.